THE THE EFFECT OF INTEREST RATE, ADMINISTRATIVE FEES, AND RISK ON ONLINE LENDING DECISIONS ON FINTECH LENDING APPLICATIONS - Sidharta, Yudi; Nurdina, Nurdina; Putri, Nabila Maulidya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study aims to determine and analyze the effect of interest rate variables, administrative costs, and risk on online loan-taking decisions. The approach used is quantitative method with primary data obtained through questionnaires. The research population includes all borrowers on the fintech lending platform in Surabaya City, while the research sample consists of borrowers of fintech lending applications (Akulaku and Kredivo) in Surabaya City (272 samples). The sampling technique used was purposive sampling. This study contributes by integrating the influence of interest rates, administrative costs, and risk in one model to understand the collective influence on fintech lending user decisions. In addition, this study fills the gap of previous research by analyzing the contradictions in the results of previous studies related to the factors that influence credit decisions, as well as presenting a new perspective with a focus on fintech lending platforms in Surabaya City. The results showed that the variables of interest rates, administrative costs, and risk affect the decision to take online loans